Pertanggungjawaban Pidana Pelaku Penganiayaan terhadap Juru Tagih (Studi Putusan Pengadilan Tinggi Palembang Nomor 261/PID/2019/PLG) - Alvina, Alvina; Rahaditya, Rahaditya (UNES Law Review, 2023)
This study are supposed to determine the criminals' criminal responsibility of persecution of debt collectors by using a case study of the Palembang District Court Decision Number 261/PID/2019/PLG. This research uses research on normative juridical that is done through looking at and studying library materials and laws and regulations or legal materials which include primary legal sources, secondary legal entities, and tertiary legal entities. This research uses a statute approach and case approach. Primary legal sources being used in this study are the 1945 Constitution of the Republic of Indonesia, Law Number 1 of 1946 on the Criminal Code, and Law Number 8 of 1981 on Criminal Procedure. Analysis method in this study is qualitative juridical analysis method. Based on the findings of this study, it could be stated if the maltreatment can cause victim unable to do his work due to the pain experienced, but does not result in serious injury or is not intended to result in serious injury, the maltreatment can be punished under Article 351 paragraph (1) of the Criminal Code or Article 466 paragraph (1) of the Criminal Code.